Teachers' Perception and Readiness Towards Adaptive Learning in the COVID-19 Pandemic: Thematical Content Analysis Study - Zulmi Ramdani; Maulia Depriya Kembara; Leli Alhapip; Andi Amri; Jaka Warsihna; Zulfikri Anas (STAI Hubbulwathan Duri, 2021)
Technological advances and life dynamics that are changing so fast and so volatile become challenges for teachers to implement their best learning model at every level of education. The study aims to explore the perception and readiness of teachers in conducting adaptive learning in pandemic times. A qualitative research method with thematic content analysis models was used to answer these objectives. A total of 327 respondents who worked as teachers were involved in filling out online questionnaires, and the selection of respondents was carried out with purposive sampling techniques. The results show a diverse perception of respondents regarding changes that occurred in the learning process, and the perception of those changes must be faced with readiness and adaptive. Teachers' readiness could be seen from their strategies that were quite effective in dealing with existing changes. These results also emphasize that respondents realized that face-to-face learning was still considered adaptive learning for them to deliver the material. Meanwhile, teachers felt that an adaptive learning guide was needed to guide the learning process when the change occurred. This study provides a clear picture of the learning concepts needed now and is an early indicator informing adaptive learning guidebooks.